The Higher Inherent Therapeutic Potential of Biomaterial-Based hDPSCs and hEnSCs for Pancreas Diseases - Xu, Bingbing; Yuan, Fu-Zhen; Lin, Lin; Ye, Jing; Fan, Bao-Shi; Zhang, Ji-Ying; Yang, Meng; Jiang, Dong; Jiang, Wen-Bo; Wang, Xing; Yu, Jia-Kuo (Frontiers in Bioengineering and Biotechnology, 2020)
Human endometrial stem cells (hEnSCs), dental pulp stem cells (hDPSCs) and adipose tissue-derived stem cells (hADSCs) are considered to be the promising candidates for the treatment of pancreas diseases. The prognosis is better with in situ injection of mesenchymal stem cells (MSCs) to the damaged pancreas compared with intravenous injection. However, the clinical application of these cells are limited, due to poor engraftment of transplanted cells after delivery. On the other hand, understanding the role of the biomaterials in cell therapy is essential to promote the therapeutic effects of MSCs. Matrigel, a basement membrane matrix biomaterial, is rich in laminin and collagen IV. The aim of this study is to investigate the difference of biological characteristics of hEnSCs, hDPSCs and hADSCs in vitro and their survival situation with Matrigel post intrapancreatic transplantation in vivo. Our findings showed, firstly, there was no significant difference in morphology and immunophenotype of these MSCs. Secondly, the biological properties, including cell proliferation, the ability of adipogenic and osteogenic differentiation and the mRNA expression levels of pancreas development-related genes, have been showed distinct difference among these MSCs. Thirdly, Matrigel can improve the survival of MSCs in vivo, especially for Matrigel-based hDPSCs and Matrigel-based hEnSCs in pancreas parenchyma of SD rats. These results suggest that hDPSCs and hEnSCs are with the greater inherent therapeutic potential for pancreas diseases compared with hADSCs.